2020
DOI: 10.21608/adjg.2020.31646.1273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Actilux - Activated Whitening Toothpaste and Marine Salts on Color Change and Microhardness of Bovine Enamel

Abstract: Purpose: To evaluate the effect of Actilux-activated whitening toothpaste and Marine salts powder on color change and microhardness of bovine enamel. Methods: Thirty intact bovine incisors were used in this study to produce enamel specimens. The specimens were randomly distributed into three groups (n= 10) according to the tested whitening agents as follows: Group I: BW; BlanX LED White Shock (Actiluxactivated), Group II: MS; Marine salts whitening powder and Group III: CR; Crest regular fluoridated toothpaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…Moreover, its special LED light accelerator activates the photocatalytic active ingredient of Actilux that destroy the stain molecules and lasts all day to naturally whiten the teeth as reported by the manufacturer. These results were in agreement with previous studies (25,26) which reported that BlanX toothpaste had a significant whitening effect on enamel.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, its special LED light accelerator activates the photocatalytic active ingredient of Actilux that destroy the stain molecules and lasts all day to naturally whiten the teeth as reported by the manufacturer. These results were in agreement with previous studies (25,26) which reported that BlanX toothpaste had a significant whitening effect on enamel.…”
Section: Discussionsupporting
confidence: 94%